Neural Malware Control with Deep Reinforcement Learning - Wang, Yu; Stokes, Jay; Marinescu, Mady (IEEE Military Communications Conference (MILCOM), 2019)
Antimalware products are a key component in detecting malware attacks, and their engines typically execute unknown programs in a sandbox prior to running them on the native operating system. Files cannot be scanned indefinitely so the engine employs heuristics to determine when to halt execution. Previous research has investigated analyzing the sequence of system calls generated during this emulation process to predict if an unknown file is malicious, but these models often require the emulation to be stopped after executing a fixed number of events from the beginning of the file. Also, these classifiers are not accurate enough to halt emulation in the middle of the file on their own. In this paper, we propose a novel algorithm which overcomes this limitation and learns the best time to halt the file's execution based on deep reinforcement learning (DRL). Because the new DRL-based system continues to emulate the unknown file until it can make a confident decision to stop, it prevents attackers from avoiding detection by initiating malicious activity after a fixed number of system calls. Results show that the proposed malware execution control model automatically halts emulation for 91.3% of the files earlier than heuristics employed by the engine. Furthermore, classifying the files at that time significantly improves the classifier's accuracy. This new model improves the true positive rate by 61.5%, at a false positive rate of 1%, compared to the best baseline classifier.